Multiple accessory tragi in a male child - Daniel, Samuel Jeyaraj; Ganesh, J. Balaji; Saranya, S.; Desingh, K. (International Journal of Research in Dermatology, 2025)
Accessory tragus (AT) is a congenital abnormality of the external ear which was first described by Birkett in 1858. AT is typically found in the preauricular region, though it can also occur less commonly in the mandibular or cervical regions. This cartilaginous protrusion, commonly known as the preauricular tag, is a rudimentary tag of ear tissue. With an incidence rate of 0.2-0.5%, this abnormality is believed to be an autosomal dominant hereditary condition caused by an abnormality in the development of first or second branchial arch. Patients with accessory tragus are more likely to be males and typically appear unilaterally. It may exist alone or in groups with a distinct morphology and location. Here, we report a case of multiple accessory tragi in a male child affecting the tragus and cheek with no other malformations.